2008
DOI: 10.1080/02533839.2008.9671376
|View full text |Cite
|
Sign up to set email alerts
|

Copper distribution for contaminated soils and acid wash efficiency

Abstract: Current application of acid washing is to practice fractionation of soil based on particle size prior to washing. However, there is little published information concerning the relationship between the cost-effectiveness of this practice and soil characteristics; this shortage contributes to less than adequate application of washing in most remediation jobs in Taiwan. This research collected soil samples from a copper-contaminated agricultural field in central Taiwan to study the cleansing efficiency of using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…As a result, heavy metals and arsenic in clays are difficult to remove due to their strong adsorption. Cheng et al (2008) indicated that the concentration of Cu in clays was as high as 670.6 mg/kg, 4.77 times the concentration achieved in gravel. Gong et al (2013) drew a similar conclusion in a soil survey in Hainan, wherein the smallest fraction (<0.053 mm) had the highest heavy metal concentrations.…”
Section: Introductionmentioning
confidence: 95%
“…As a result, heavy metals and arsenic in clays are difficult to remove due to their strong adsorption. Cheng et al (2008) indicated that the concentration of Cu in clays was as high as 670.6 mg/kg, 4.77 times the concentration achieved in gravel. Gong et al (2013) drew a similar conclusion in a soil survey in Hainan, wherein the smallest fraction (<0.053 mm) had the highest heavy metal concentrations.…”
Section: Introductionmentioning
confidence: 95%